An Analysis Of Noun Types In President Prabowo Subianto’s Speech On State Asset Repossession In The Jakarta Post - Sinaga, Riyanti Anjelina; Tambunan, Naomi Arta; Sitanggang, Yolanda Jessica; Simorangkir, Tessaria; Sinaga, Mutiara Angelica; Sitanggang, Anita (Universitas Pahlawan Tuanku Tambusai, 2025)
Language plays a crucial role in shaping political discourse, especially through the use of specific grammatical structures such as nouns. This study analyzes the types and functions of nouns used in President Prabowo Subianto’s speech delivered on May 1, 2025, during the Labor Day rally in Jakarta. The speech focuses on the government's plan to reclaim state assets from private control, presenting a message embedded with nationalistic and constitutional themes. Using a qualitative descriptive method with content analysis, the study classifies nouns in the speech into eight categories: common, proper, concrete, abstract, countable, uncountable, collective, and compound nouns. Data were collected from a published version of the speech on The Jakarta Post website and analyzed sentence by sentence to identify each noun and its type. The results revealed a total of 188 nouns across 15 core sentences. Common nouns were the most frequently used (34.6%), followed by countable nouns (24.0%) and proper nouns (16.0%). The presence of abstract nouns (14.9%) and compound nouns (10.6%) highlighted the ideological and policy-oriented content of the speech. These findings suggest that President Prabowo’s noun choices were intentional and strategically used to legitimize political actions, construct national identity, and appeal to public sentiment. This study contributes to the field of applied linguistics, particularly in political discourse analysis, by demonstrating how linguistic forms especially nouns serve as tools of persuasion, authority, and ideology in political communication.